Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Four students are trying to find the rule that translates point [tex]\(N(-2,-4)\)[/tex] to [tex]\(N^{\prime}(2,4)\)[/tex]. Each student's reasoning is shown below.

Raheem: The rule is [tex]\((x \cdot(-1), y \cdot(-1))\)[/tex] because [tex]\(-2 \cdot(-1) = 2\)[/tex] and [tex]\(-4 \cdot(-1) = 4\)[/tex].

Casey:

Andrew: The rule is [tex]\((x+2, y+4)\)[/tex] because the image is [tex]\((2,4)\)[/tex].

Lo: The rule is [tex]\((x+4, y+0)\)[/tex] because the coordinates are opposites.

Which student is correct?

The rule is [tex]\((x+4, y+8)\)[/tex] because [tex]\(-2 + 4 = 2\)[/tex] and [tex]\(-4 + 8 = 4\)[/tex].

A. Raheem
B. Casey
C. Andrew
D. Lo


Sagot :

Let's analyze the reasoning of each student and determine who correctly translates the point [tex]\( N(-2, -4) \)[/tex] to [tex]\( N^{\prime}(2, 4) \)[/tex].

1. Raheem: Raheem suggests the rule [tex]\( (x \cdot (-1), y \cdot (-1)) \)[/tex].
- Applying this rule to the point [tex]\( N(-2, -4) \)[/tex]:
- [tex]\( x = -2 \)[/tex], so [tex]\( x \cdot (-1) = -2 \cdot (-1) = 2 \)[/tex]
- [tex]\( y = -4 \)[/tex], so [tex]\( y \cdot (-1) = -4 \cdot (-1) = 4 \)[/tex]
- The result is the point [tex]\( (2, 4) \)[/tex], which matches [tex]\( N^{\prime}(2, 4) \)[/tex].

2. Andrew: Andrew suggests the rule [tex]\( (x + 2, y + 4) \)[/tex].
- Applying this rule to the point [tex]\( N(-2, -4) \)[/tex]:
- [tex]\( x = -2 \)[/tex], so [tex]\( x + 2 = -2 + 2 = 0 \)[/tex]
- [tex]\( y = -4 \)[/tex], so [tex]\( y + 4 = -4 + 4 = 0 \)[/tex]
- The result is the point [tex]\( (0, 0) \)[/tex], which does not match [tex]\( N^{\prime}(2, 4) \)[/tex].

3. Lo: Lo suggests the rule [tex]\( (x + 4, y + 0) \)[/tex].
- Applying this rule to the point [tex]\( N(-2, -4) \)[/tex]:
- [tex]\( x = -2 \)[/tex], so [tex]\( x + 4 = -2 + 4 = 2 \)[/tex]
- [tex]\( y = -4 \)[/tex], so [tex]\( y + 0 = -4 + 0 = -4 \)[/tex]
- The result is the point [tex]\( (2, -4) \)[/tex], which does not match [tex]\( N^{\prime}(2, 4) \)[/tex].

4. Correct Rule: The suggested rule [tex]\( (x + 4, y + 8) \)[/tex].
- Applying this rule to the point [tex]\( N(-2, -4) \)[/tex]:
- [tex]\( x = -2 \)[/tex], so [tex]\( x + 4 = -2 + 4 = 2 \)[/tex]
- [tex]\( y = -4 \)[/tex], so [tex]\( y + 8 = -4 + 8 = 4 \)[/tex]
- The result is the point [tex]\( (2, 4) \)[/tex], which matches [tex]\( N^{\prime}(2, 4) \)[/tex].

Based on the analysis, the correct student who has found the rule that translates [tex]\( N(-2, -4) \)[/tex] to [tex]\( N^{\prime}(2, 4) \)[/tex] is Raheem.

Therefore, the answer is: Raheem.